Places of quiet beauty : parks, preserves, and environmentalism - Conard, Rebecca (American land and life series., 1997)
Resource protection and public recreation policies have always been subject to the shifting winds of management philosophy governing both national and state parks. Somewhere in the balance, however, parks and preserves have endured as unique places of mind as well as matter. Places of Quiet Beauty allows us to see parks and preserves, forests and wildlife refuges & mdash;all those special places that the term & ldquo;park & rdquo; conjures up & mdash;as measures of our own commitment to caring for the environment. In this broad-ranging book, historian Rebecca Conard examines the complexity of.